CSA-Induced PRES after Heart Transplantation—Report of Two Cases and Review - Katharina Huenges (Georg Thieme Verlag KG, 2021)
Background Posterior reversible encephalopathy syndrome (PRES) is a rare neurological disease possibly associated with the use of calcineurin inhibitors (CNI) like cyclosporine A. Case Description The case of a patient who developed severe PRES under CNI therapy shortly after heart transplantation is presented here. Cerebral computed tomography led to the diagnose of PRES in our patient. New therapy strategy with a quadruple immunosuppressive protocol (cortisone, mycophenolate mofetil, low-dose CNI, and a mechanistic target of rapamycin inhibitor) was started. Conclusion Under the quadruple therapy, a neurologic recovery occurred. In PRES, the presented alternative therapy strategy may lead to improving neurological conditions and preserved transplant organ functions.